The Australian national elections of 1977 - Penniman, Howard Rae. (Washington : American Enterprise Institute for Public Policy Research, 1979)
MS Acc05/133 comprises party meeting agendas, minutes and briefing papers, decisions of party meetings, files on elections, issues including copyright and retention of census forms, history and correspondence, and appointment diaries.
Includes bibliographical references and index.
aia 14/05/2018
Loan
Keywords: Elections; Australia $1 (BPolitics and government $1 (B1945.s; Australia